Predicting of excess body fat in children. Issue 5 (16th September 2022) - Córdoba-Rodríguez, Diana Paola; Rodriguez, Gerardo; Moreno, Luis A.
Abstract : Purpose of review: Approximately 370 million children and adolescents worldwide showed overweight or obesity in 2016. The risk of developing severe comorbidities depends on the age of onset and the duration of obesity. This review discusses available methodologies to detect excess body fat in children as well as the early life factors that predict excess body fat and its development. Recent findings: Factors, such as parental nutritional status, maternal weight gain during pregnancy, maternal malnutrition, maternal smoking during pregnancy, low and high birth weight, rapid weight gain, and short infant sleep duration have been independently and positively associated with neonatal, infant, and children adiposity. Early detection of excess body fat in children through the use of various tools is the first step in preventing nutrition-related diseases in adulthood. Summary: The early detection of excess body fat and the implementation of efficient interventions to normalize the weight of children and adolescents at obesity risk are essential to prevent diseases in adult life.